The Motif of Laziness in the Friendly Correspondence of the Young I.V. Kireevsky - Marina D. Kuzmina (Studia Litterarum)
The article examines the motif of laziness in the friendly correspondence of I.V. Kireevsky in the 1820s–1830s. It turns out that for the future Slavophile the interpretation of this motif, which was widespread in Russian lyric poetry and epistolary of the early 19th century, remained relevant. It was authentic, in particular, for the young A.S. Pushkin — as “blessed laziness” accompanying a creative gift and therefore fruitful, associated with the freedom and happiness of creativity. In many ways, Kireevsky perceived such an understanding of laziness through the prism of romantic culture, and particularly of elegiac romanticism under the influence of its major representative V.A. Zhukovsky, his relative and friend. At the same time, the young epistolographer also adopted the understanding of laziness of his correspondents, such as A.I. Koshelev, A.V. Venevitinov, V.F. Odoevsky and etc. From their point of view, laziness in the chosen field of activity for the good of the Fatherland and laziness in friendly correspondence, where, in fact, it is necessary to report on the results of this activity, is completely unacceptable. Consequently, lack of zeal in correspondence is disturbing because it may indicate lack of zeal in activity. Kireevsky has earned a reputation as an idler among his friends. And, on the one hand, he defended freedom of creativity, the right to internal work in the absence of external work, but on the other hand, he worried and repented in front of his friends in laziness, tried to fight it. The motif of laziness has become the main artistic experiments and achievements of Kireevsky as the epistolographer.